2021
DOI: 10.1002/jctb.6745
|View full text |Cite
|
Sign up to set email alerts
|

Insights into polyester plastic biodegradation by carboxyl ester hydrolases

Abstract: Environmental pollution caused by polyesters has become a major ecological safety concern that needs to be managed urgently. One way to resolve this problem is giving the spotlight to current emerging research of microbial biocatalysts. During the last two decades many researchers have reported the ability to break down and modify natural and synthetic polyesters using different microbial carboxyl ester hydrolases (lipases, esterases, cutinases, PETases, etc.) also called polyesterases, and contribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 270 publications
1
28
0
Order By: Relevance
“…The protein RPA1511 isolated from Rhodopseudomonas palustris has the catalytic triad residues, which are important for the hydrolysis of both monoester and polyester substrates. It was considered to be critical for the hydrolysis of PLA and was active in catalyzing solid PLA with the production of lactic acid monomers, dimers, and larger oligomers ( Hajighasemi et al, 2016 ; Gricajeva et al, 2021 ). Moreover, some functions related to the carbon, nitrogen, and sulfur metabolic pathways were revealed by FAPROTAX, which indicated that BDMs may affect the biogeochemical cycling of elements in agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The protein RPA1511 isolated from Rhodopseudomonas palustris has the catalytic triad residues, which are important for the hydrolysis of both monoester and polyester substrates. It was considered to be critical for the hydrolysis of PLA and was active in catalyzing solid PLA with the production of lactic acid monomers, dimers, and larger oligomers ( Hajighasemi et al, 2016 ; Gricajeva et al, 2021 ). Moreover, some functions related to the carbon, nitrogen, and sulfur metabolic pathways were revealed by FAPROTAX, which indicated that BDMs may affect the biogeochemical cycling of elements in agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic polyester plastics may be hydrolyzed by microbial lipases, carboxylesterases, and cutinases, which can therefore be collectively referred to as polyesterases ( Gricajeva et al, 2021 ). Many polyesterases are PET hydrolyzing enzymes (PHEs), although cutinases are considered most effective in cleaving polyester bond linkages ( Kawai et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in this special issue, the degradation and conversion of various emerging pollutants, including polyaromatic hydrocarbons, poly (ε-caprolactone), 5-hydroxymethyl furfural, plastic, polyesters, using microbes and enzymes have been well described. [1][2][3][4][5][6][7][8][9][10][11][12] In addition to this various biomass, biopolymers including lignin, cellulose, and municipal-, industrial-, and agricultural-based pollutants were documented to convert into valuable products using enzymatic pathways. [13][14][15][16] The cutting-edge technologies of protein engineering and directed evolution have already minimized the cost of enzymatic transformation processes with higher product yield.…”
Section: Microbial Enzymes For Green Energy and Clean Environmentmentioning
confidence: 99%